PRODUKSI FILM MIKRO WISATA KOLABORASI FORUM FILM DESA - Adji, Titus; Soepono Adji, Titus; Adji, Titus Soepono Adji; Prajanata Bagiananda Mulia; Dafa Satriyo Putra (Journal of Applied Community Engagement, 2025)
Rural film production holds strategic potential as a medium of community expression, yet its sustainability is often constrained by limited funding. Positioned as civic media (Jenkins et al., 2016) and a form of visual agency (Pink, 2007), rural films can strengthen local identity while creating economic opportunities through film-induced tourism (Beeton, 2006). Under micro-budget conditions, production requires resource-based creativity (Mahaffy, 2025; Greenberg, 2022), making alternative financing models such as crowdfunding and community-driven gotong royong (Belleflamme et al., 2014) essential. This study employs Participatory Action Research (Reason & Bradbury, 2008; McIntyre, 2007) by establishing the Rural Film Forum as a collaborative space linking film communities, local businesses, government, and academics. The forum facilitates resource mapping and co-production between local film community and other local partners. Findings show that collective financing not only addresses funding gaps but also increases social participation, indicating that sustainable rural film production relies on collaborative ecosystems and can serve as an instrument for community empowerment and tourism promotion.